Functional outcome of diaphyseal fractures of forearm in children treated with titanium elastic nailing system - Hossain, Kazi Shahadat; Rafi, Abdullah Al; Rabbi, Qaisur; Mia, M. Shoeb; Kawchar, M. Abdur Rouf (International Journal of Research in Orthopaedics, 2024)
Background: Forearm fractures are common injuries in children, with diaphyseal fractures of the forearm being among the most frequent injuries treated in the pediatric population. This study aimed to assess the functional outcome of diaphyseal fractures of the forearm in children treated with the titanium elastic nailing system. Methods: This prospective observational study was conducted at the Department of Orthopaedics, Mainamoti Medical College, Cumilla, Bangladesh from January 2020 to December 2022. The study included 67 patients aged 6-15 with diaphyseal forearm fractures treated with the titanium elastic nailing system, selected through purposive sampling. MS Office tools were used for data analysis. Results: According to the functional outcome criteria described by Price et al., it was observed that in the highest number of patients (86.56%), the functional outcome was excellent, followed by good, fair, and poor outcomes found in 8.96%, 2.99%, and 1.49% of the cases, respectively. As the postoperative complications, the delayed union was found among 4%, and skin infection was found among 3% of cases. Conclusions: Considering the excellent outcomes and lower complication rate, the titanium elastic nailing system may be considered a very effective and safe treatment method for the management of diaphyseal fractures of the forearm in children.